Investigation of the electrical conductivity of sintered monoclinic zirconia (ZrO2). Issue 11 (1st August 2017) - Kwon, Oh Hyun; Jang, Changheui; Lee, Junho; Jeong, Hu Young; Kwon, Young-il; Joo, Jong Hoon; Kim, Hongjin
Abstract: High-density monoclinic ZrO2 was manufactured through sintering at ~1200 °C by using nanosized powders. Then, the electrical conductivity was measured at a range of high temperatures (700–900 °C) by electrical impedance spectroscopy (EIS). For the as-sintered monoclinic ZrO2, the measured electrical conductivity was 3.2×10 −5  s/cm (for 80% TD) and 4.4×10 −5  s/cm (for 89% TD) at 900 °C. After aging at 900 °C for 100 h, the electrical conductivity of the monoclinic ZrO2 of 80%-TD decreased by more than 50%. However, after reheating at 1200 °C for 1 h, approximately 80% of the conductivity was recovered compared to the value of the as-sintered monoclinic ZrO2 . The pure monoclinic crystal structure was retained despite the aging and reheating treatment. Based on microstructural observations of the aged and reheated monoclinic ZrO2, the changes in electrical conductivity after aging and reheating were explained by the formation and recovery of micro-cracks, respectively.